The politics of war reporting authority, authenticity and morality - Markham, Tim, 1974- (Manchester University Press : Distributed to the United States exclusively by Palgrave Macmillan, 2011)
This book unpacks the aspects of the lives of war correspondents, exposing the principles of interaction and valorisation that usually go unacknowledged. This book asks why it is that the authoritative reporter increasingly needs to appear authentic, and that success depends not only on getting things right but being the right sort of journalist. This depends on the uncalculating mastery of practices both before and during a journalist's career. Includes interview with war correspondents and others with an active stake in the field and combines them with the critical sociology of Pierre Bourdieu to construct a political phenomenology of war reporting, the power relations and unspoken rules underpinning the representation of conflict and suffering by the media.